PENGARUH PENDEKATAN KEADILAN ORGANISASI (ORGANIZATIONAL JUSTICE) TERHADAP KINERJA PEGAWAI PADA DINAS PERINDUSTRIAN DAN PERDAGANGAN KOTA SAMARINDA - Muhammad Darham; Achmad Djumlani; Muhammad Jamal Amin (Jurnal Administrative Reform, 2017)
The problem formulated in this paper is whether organizational justice which includes distributive justice, procedural justice and interactional justice significant effect on the performance of employees either partially or simultaneously and which one of them has the dominant influence on employee performance. The results show that there is a significant influence between independent variables of organizational justice (Justice Organization) which includes distributive justice, procedural justice and interactional justice on the dependent variable (performance of employees).